2018
DOI: 10.1111/jam.13914
|View full text |Cite
|
Sign up to set email alerts
|

The changes in dominant lactic acid bacteria and their metabolites during corn stover ensiling

Abstract: The knowledge about the ecological succession of the dominant lactic acid bacteria could lead to improved ensiling practices and the selection of corn stover silage inoculants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…Thus, lactic acid‐rod ( Lactobacillus ) plays an important role for pH reduction at the later stage (Ni et al, ). Xu, Zhang, Zhang, Li, and Kong () reported the P. pentosaceus peaking at 6 days, and then rapidly disappeared afterward, whiles Bao et al () ensiled alfalfa inoculated with Pediococcus acidilactici and Lactobacillus plantarum , found Pediococcus and Lactobacillus became the dominant genera after 35 days fermentation, which was similar to our results. Erwinia indicates similarities to Enterobacteria and is restricted to bacteria which are pathogenic to plants (Starr & Chatterjee, ).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, lactic acid‐rod ( Lactobacillus ) plays an important role for pH reduction at the later stage (Ni et al, ). Xu, Zhang, Zhang, Li, and Kong () reported the P. pentosaceus peaking at 6 days, and then rapidly disappeared afterward, whiles Bao et al () ensiled alfalfa inoculated with Pediococcus acidilactici and Lactobacillus plantarum , found Pediococcus and Lactobacillus became the dominant genera after 35 days fermentation, which was similar to our results. Erwinia indicates similarities to Enterobacteria and is restricted to bacteria which are pathogenic to plants (Starr & Chatterjee, ).…”
Section: Discussionsupporting
confidence: 90%
“…Second, the acidity resulting from heterofermentative Weissella is weaker in comparison with homofermentative LAB because they produce one mole of LA, one mole of carbon dioxide, and either a mole of ethanol or AA from each mole of glucose fermented, whereas homofermentative LAB produce two moles of LA (Muck, ). Third, the fermentation characteristics will generally improve with a higher percentage of homofermentative Lactobacillus in silage (Keshri et al, ; Xu, Zhang, Zhang, Li, & Kong, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the LAB population in silage inoculated with LpE on all ensiling days were higher (P < 0.05) than that in silages inoculated with CIA, CIB and control ( Fig. 2A), which might be attributed to the supplementation of fibrolytic enzymes that can degrade the structural carbohydrates of silage into fermentable sugars that supports the growth of LAB 35,36 . In agreement, Colombatto et al demonstrated that the addition of cellulase enzymes and L.plantarum could effectively prompt the LAB fermentation and improve the silage quality 37 .…”
Section: Effect Of Different Microbial Inoculants On Microbial Countsmentioning
confidence: 93%